Comparative biomechanical analysis of the rotational shot put technique - Coh, M.; Štuhec, S.; Supej, M. (Collegium Antropologicum, 2008)
The study aimed to establish the modalities of the rotational shot put technique of two elite shot putters with substantially different constitutional characteristics. A biomechanical analysis of the technique was carried out using the APAS 3-D kinematic system, whereby a 15-segment model of shot putters was defined by 18 reference points. To enable the calculation of the kinematic and dynamic parameters, independent routines were programmed by the Matlab software. Anthropometric characteristics were established on the basis of 15 variables measured by the International Biological Programme (IBP) procedure. The results of the study revealed some differences between the athletes in terms of their mesomorphic constitutional component, body mass index, circular measures of the lower and upper extremities and the muscular, fat and bone mass. The technique models of both shot putters differ mostly in terms of the following kinematic and dynamic parameters: absolute release velocity, height of release, maximum angular velocity of the elbow of the throwing arm, trajectory of the centre of gravity of the body and the shot, torsional rotation of the shoulder axis relative to the hip axis, maximum force applied to the shot, kinetic energy and the kinetic energy differential of the shot.